(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Case Summary: An 84-year-old man was admitted to the hospital due to seizure episodes. One week before the patient was admitted to the same hospital with complaints of COPD exacerbation and was discharged with a prescription of levofloxacin, theophylline ceftriaxone, pantaprazole, montelukast, methylprednisolone, budesonide nebulization, ipratropium bromide nebulization, and syrup codylex. After receiving one dose of oral levofloxacin, the patient experienced a seizure. The patient was hyperglycaemic at the time of admission and had no history of a seizure disorder. Discussion: Here the cause of seizure could be a drug-drug interaction (between theophylline and levofloxacin) with CYP1A2 substrates with no epileptogenic effects which could augment the concentration of levofloxacin and consequently results in seizures. In spite of that, it has to be kept in mind that the drug-drug interactions originate at various pharmacodynamic and pharmacokinetic levels and that drugs CYP affinities are rarely completely CYP-specific. Thus levofloxacin may have drug interactions at the level of CYPs other than CYP1A2. Conclusion: the clinicians are advised to closely monitor the possibility of seizures in COPD patients who+ are taking both levofloxacin and theophylline. The physicians should also be encouraged to use the techniques of TDM to individualize the dose of narrow therapeutic drugs to avoid serious adverse effects.